Technology Adoption and Productivity Growth: Evidence from Industrialization in France - Juhász, Réka; Squicciarini, Mara P.; Voigtländer, Nico (Journal of Political Economy, 2024)
New technologies tend to be adopted slowly and – even after being adopted – take time to be reflected in higher aggregate productivity. One prominent explanation for these patterns is the need to reorganize production, which often goes hand-in-hand with major technological breakthroughs. We study a unique setting that allows us to examine the empirical relevance of this explanation: the adoption of mechanized cotton spinning during the First Industrial Revolution in France. The new technology required reorganizing production by moving workers from their homes to the newly-formed factories. Using a novel hand-collected plant-level dataset from French archival sources, we show that productivity growth in mechanized cotton spinning was driven by the disappearance of plants in the lower tail – in contrast to other sectors that did not need to reorganize when new technologies were introduced. We provide evidence that this was driven by organizational challenges such as developing optimal plant layout. A process of ‘trial and error’ led to initially low and widely dispersed productivity, and – in the subsequent decades – to high productivity growth as knowledge diffused through the economy and new entrants adopted improved methods of organizing production.